Romanian Accounting Students’ Perceptions of Online Learning during Pandemic Period - Alina Beattrice VLADU; Dan Dacian CUZDRIOREAN; Szilveszter FEKETE (Communications of International Proceedings, 2022)
Due to the COVID-19 pandemic, the online learning process has become prevalent in Romanian universities. In this regard, it is extremely important to understand students` perspectives, experiences, and preferences in the distance learning process. We surveyed the largest public university in Romania. As such, randomly selected participants were asked to complete an online questionnaire assessing the effectiveness of the distance learning process. Data collected from the survey were analyzed with routine statistical software. Our results document that students encountered multiple negative experiences (e.g., lack of social interaction and competence, technical issues, lack of motivation, less activity compared to face-to-face education, etc.). Although our respondents agreed on the advantages of online learning, a large majority considered that this type of learning cannot substitute face-to-face learning. According to our results, blended learning is the most appropriate for providing a rigorous learning environment. Our findings may help higher education institutions to improve the distance learning process. Future research avenues are also approached.
Keywords: Students` perceptions; online learning; Covid-19 pandemic